Mathematical model of gonorrhea in a hetero sexuals with time dependent population - Ramakishore, R (Journal of Experimental Sciences, 2012)
This paper deals with a mathematical model of gonorrhea among hetero-sexual. This model composed of males and females is characterizes growth rates of promiscuous population (P), Infective male population (I1), and Infective female population (I2). In all three equilibrium points are identified for the system under investigation, the criterion for the asymptotic stability of all three possible equilibrium points is derived of those, purely healthy state is stable under the condition F.M <1 and co-existence state is stable with the condition F.M >1.